(Nahj al Balaghah) ’s psychological scope ...The cuteness Expression in Death Vocabulary as a sample.... - Ali Sadiq jafar - Fakher Hasham saad Alyasiri ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
Language shows what is in the soul of feelingsand emotions. If a person is psychologically affected by something, we find itsThe echo in language. Therefore, the choice of vocabulary according to its psychological dimension has an impact on the sender and the recipient. Hence, the expression’s subtlety stems from the psychological impact of the vocabulary. This effect is one of the reasons for its formation and reference to it.. There are vocabulary that counteracts pessimism and superstition when we mention them explicitly, including the vocabulary of death, because death is the reality of the end of a person’s life and his departure from life,; therefore,, we find Imam Ali bin Abi Talib( peace be upon him) deliberately using alternative vocabulary for death for the sake of the cuteness of expression..